PERBANDINGAN MODEL ANDREASSEN DAN MODEL ARTIFICIAL NEURAL NETWORK UNTUK PREDIKSI FATALITAS KORBAN KECELAKAAN LALULINTAS - Agus, Supratman (Jurnal Transportasi, 2012)
In ASEAN, Indonesia has largest area and population, longest road infrastructure, and largest number of motor vehicles, but road victimsâ fatality is low. This indicates under-reporting. Existing model of road victimsâ fatality is Andreassen models which use population numbers and motor vehicles numbers asvariables to prediction numbers of fatality. This study aimed to obtaining the best predictive model of road victimsâ fatality which suits Indonesiaâs conditions. Three models were compared are Andreassen model, Artificial Neural Network with two variables (ANN2) and four variables (ANN4), with driving license holderand road length as two additional variables. Model validation was performed on three cities in West Java with different categories population densities. The results reveal that ANN4 is the best fatality prediction model. In addition, predictions of road victim numbers in Indonesia are not only influenced by populationand vehicles number, but also by driving license holder numbers and road length.Keywords: fatality, model comparison, Andreassen model, Artificial Neural Network model